Optimizing business growth: the impact of integrated sales and marketing teams with strategic training programs - Wingert-Dudley, Claire (My University, 2025)
The synergy between sales and marketing teams plays a pivotal role in driving sustainable and profitable business growth. This thesis explores the strategic benefits of integrating these siloed functions, with a particular focus on the impact of cross-training and collaboration initiatives. Through the analysis of original survey data collected from 150 sales and marketing professionals across various industries, this research examines how structured training programs and sales-marketing alignment influence key performance indicators. Using regression analysis, the study finds that organizations investing in continuous training and fostering interdepartmental collaboration report improvements in profitability, operational efficiency, and customer satisfaction. While training investment emerged as a statistically significant predictor of positive business outcomes, collaboration showed less direct influence when measured independently. Employee engagement and retention were found to be positively facilitated by job satisfaction, which itself was shaped by the presence of ongoing coaching and regular training touchpoints. The findings underscore the importance of a strategic approach to team integration, suggesting that companies that align their sales and marketing functions improve internal cohesion and overall financial impact. This thesis contributes to a growing body of evidence that collaboration and capability-building are key drivers for long-term growth and competitive advantage.
Keywords: Sales; Marketing; Training; Collaboration; Training programs; Sales and marketing integration